(3QSGdI aj GdcjejGA hGdCMLGQ GdcQjeIs
(3BNQgG (B:s
(3hgh jbhd (B: (3QMec Gddg ceG QMeJfi GdMeO ddg GdPi CPgH YfG GdMRf Ef QHfG dZahQ TchQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B3 - (3U(B5s
(3GdfSNI HgG MhGTs
(3eQJHI Ydi YTQI aUhd hChd eG ajgG ef bHjd GdaUd GdChd hgh ai eYQaI GdLhgQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B57 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs